(untitled) (المجلة الدولية للبحوث العلمية, 2024)
This paper explores the legal protections afforded to shareholders of unlisted joint stock companies in Saudi Arabia during merger and acquisition activities. There are significant risks associated with using tools like mergers and acquisitions, including market share loss and decreased profitability for shareholders. Thus, this study aims to analyse the Saudi Companies Law for potential gaps that may affect shareholder legal protections. The researchers primarily use a doctrinal legal methodology to assess the legal framework. This approach provides that the study is based on an examination of the legal framework of Saudi Arabia such as statutes, rules, principles, and cases[1]. It will also apply the analytical approach to evaluate the legal framework’s fundamentals, conceptual problems, and practical effects, to make sure that the study finds opportunities for improvement. The Article identifies the differences between unlisted and listed companies concerning document disclosure requirements, lack of the method used for asset valuation, lack of forward-looking information disclosure, the absence of obligatory independent financial reports and unclear definitions of shareholder rights to oppose or exit mergers and acquisitions at fair value. The study found that these areas represent potential gaps that could undermine shareholders of unlisted joint stock, improvements to the law, such as the adoption of independent valuation standards, mandatory financial disclosures, and clearer expression of shareholder rights.